A Clinico-Epidemiological Study on Green Pit Viper Bite Attending Chittagong Medical College Hospital (Journal of Medicine, 2025)
Background: Snakebites are a neglected public health issue, particularly in rural tropical areas. In Bangladesh, Green Pit Viper bites are common, causing pain, swelling, and coagulopathy, leading to morbidity. Epidemiology of Green Pit Viper biting, frequency of coagulopathy and proper description of clinical features from Green Pit Viper bite is lacking.  This study aims to describe clinical features, coagulopathy patterns, pre-hospital management, and outcomes of patients admitted with Green Pit Viper bite in Chittagong Medical College Hospital. Method: This study was cross-sectional and observational, analyzing medical records and data from the Snakebite Clinic at Chittagong Medical College Hospital (CMCH) in Bangladesh from 1st May 2017 to 30th April 2018. Informed written consent was obtained from patients, and their epidemiological data and clinical findings were recorded in a predefined case report form. The swelling extent was measured by comparing it to the non-bitten limb, and a 20-minute whole blood clotting test (WBCT) was performed in all patients to detect and monitor coagulopathy. Lab coagulation profiles were used to confirm coagulopathy and its reversal. Statistical analysis was conducted using SPSS-23. Results: The study included 112 patients with a median age of 32 years, predominantly adult males from rural areas. Bites commonly occur during outdoor activities. Pre-hospital management practices were widespread, with tourniquets and herbal remedies being common. Swelling was the primary local effect. Notably, 43% of patients developed coagulopathy, often with delayed onset. Most patients reached the hospital within 5 hours of the bite. Coagulopathy reversal was observed, and the majority of patients improved. Conclusions: This study sheds light on Green Pit Viper bites in Bangladesh, emphasizing coagulopathy's significance and the need for specific antivenom.J MEDICINE 2025; 26: 28-35